Control and Insecurity in Australian and Canadian Universities during the COVID-19 Pandemic - Peetz, David; O’Brady, Sean; Weststar, Johanna; Coles, Amanda; Baird, Marian; Cooper, Rae; Charlesworth, Sara; Pyman, Amanda; Ressia, Susan; Strachan, Glenda; Troup, Carolyn (Relations industrielles / Industrial Relations, 2022)
We studied 14 universities across Canada and Australia to examine how the COVID-19 crisis, mediated through management strategies and conflict over financial control in higher education, influenced workers’ job security and affective outcomes like stress and happiness. The countries differed in their institutional frameworks, their union density, their embeddedness in neoliberalism and their negotiation patterns. Management strategies also differed between universities. Employee outcomes were influenced by differences in union involvement. Labour cost reductions negotiated with unions could improve financial outcomes, but, even in a crisis, management might not be willing to forego absolute control over finance, and it was not the depth of the crisis that shaped management decisions.
Keywords: Analyse comparative; Australia; Australie; COVID-19; Canada; Contrôle; Covid-19; Stratégies de gestion; Syndicat; Travailleurs universitaires; comparative analysis; control; contrôle financier; financial control; management strategies; negotiation pattern; négociation collective; union; university workers